PENGARUH PENGGUNAAN METODE PEMBELAJARAN SQ3R (SURVEY, QUESTION, READ, RECITE, REVIEW) BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR BIOLOGI SISWA PADA MATERI POKOK SISTEM PERNAPASAN MANUSIA DI KELAS XI IPA SMA NEGERI 2 TUKKA - lisa indriyani; Rabiyatul Adawiyah Siregar; Nabilah Siregar (JURNAL EDUGENESIS, 2019)
ABSTRAK This study aims to determine whether there is an influence on the use of SQ3R learning methods assisted by video learning on student biology learning outcomes in the subject matter of the human respiratory system in Tukka 2 Public High School Science XI class. This research was conducted in April-June 2019. This study used descriptive and experimental methods. The population in this study were all students of class XI IPA 2 Tukka High School consisting of 2 classes with a sample of 58 people. The sampling technique used is total sampling. The instruments used are observation and test sheets. The data obtained were analyzed by descriptive analysis and inferential statistical analysis. Based on the descriptive analysis, the average value of the use of the SQ3R learning method assisted by learning videos reached 90.5 which was included in the "Very Good" category. Biology learning outcomes of students before (pretest) using the SQ3R learning method assisted by learning videos reached an average value of 54.48 which was included in the "Less" category, while the biology learning outcomes of students after (posttest) using the SQ3R learning method assisted learning videos reached average scores was 68.70 which is included in the "Enough" category. Next is inferential statistical analysis using the "t-test" formula with the help of SPSS version 21. The test criteria used are Ha accepted and H0 rejected if the significance level is < 0.05. The results of calculations performed obtained a correlation between two variables is 0.635 with a significant of 0.00. Thus 0.00 < 0.05. This means that there is a significant influence between the use of the SQ3R learning method assisted by video learning on student biology learning outcomes in the subject matter of the human respiratory system in class XI IPA 2 Tukka Public High School. Keywords: SQ3R Method, Learning Video, Human Respiratory System, Tukka